2000
DOI: 10.1088/0031-9120/35/6/304
|View full text |Cite
|
Sign up to set email alerts
|

The A to B of quantum physics

Abstract: The authors describe the way in which quantum physics is introduced in the new AS (Advanced Subsidiary) course Advancing Physics. It is based on the sum over many paths approach developed by Richard Feynman and described at an appropriate level in his book, from which the following quotation is drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Several have adopted and expanded the approach in introductory undergraduate courses [5], teacher preparation courses [6,7], and directly with high school students [8]. In Great Britain, the ambitious large-scale project "Advancing Physics AS" [9,10] of an A-level high school course in physics produced by the Institute of Physics treated quantum physics using the sum over paths approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several have adopted and expanded the approach in introductory undergraduate courses [5], teacher preparation courses [6,7], and directly with high school students [8]. In Great Britain, the ambitious large-scale project "Advancing Physics AS" [9,10] of an A-level high school course in physics produced by the Institute of Physics treated quantum physics using the sum over paths approach.…”
Section: Introductionmentioning
confidence: 99%
“…• Elimination of difficulties in understanding quantum mechanical concepts: By considering the students' difficulties and misconceptions in understanding quantum mechanics, some researchers suggested some remedies to eliminate them by changing how quantum mechanics is taught through introducing new approaches and supporting the instruction with newly developed materials and media (Dobson, Lawrence, & Britton, 2000;Hadzidaki, Kalkanis, & Stavrou 2000;Michelini, Ragazzon, Santi, & Stefanel, 2000;Zollman, Rebello, & Hogg, 2002).…”
mentioning
confidence: 99%
“…In addition, Sadaghiani (2005) has shown that in addition to students' problems with learning quantum mechanics, the instructors have problems teaching it because of the nature of the quantum concepts. By using conceptual physics questions, previous research (Bao, 1999;Çataloğlu & Robinett, 2002;Didiş et al, , 2014Dobson et al, 2000;Escalada, 1997;Gardner, 2002;Ke et al, 2005;Kwiat & Hardy, 2000;Morgan, 2006;Müller & Wiesner, 1999Olsen, 2002;Özcan et al, 2009;Sadaghiani, 2005;Singh, 2001;Singh et al, 2006;Strnad, 1981;Styer, 1996;Wattanakasiwich, 2005) has shown that students' understanding was shaped by the abstract, counter-intuitive, and mathematical nature of the theory. This study identified the nature of quantum theory was a context-specific motivational element influencing students' motivation, so their learning the theory.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A great proportion of this research has been conducted in the cognitive domain, and research in the affective domain has only recently been conducted by focusing on achievement motivation (Didiş & Özcan, 2007;Didiş & Redish, 2010, 2012. The pedagogical research on quantum theory examines the understanding of both upperlevel high school and university-level physics students, and provides new methodologies about quantum mechanics instruction (Bao, 1999;Budde, Niedderer, Scott, & Leach, 2002a, 2002bCuppari, Rinaudo, Robutti, & Violino, 1997;Çataloğlu & Robinett, 2002;Didiş, 2015;2014;Dobson, Lawrence, & Britton, 2000;Escalada, 1997;Frederick, 1978;Gardner, 2002;Hadzidaki, Kalkanis, & Stavrou, 2000;Ireson, 2000;Kalkanis, Hadzidaki, & Stavrou, 2003;Ke et al, 2005;Kwiat & Hardy, 2000;Mannila, Koponen, & Niskanen, 2002;Michelini, Ragazzon, Santi, & Stefanel, 2000;Morgan, 2006;Müller & Wiesner, 1999Olsen, 2002;Özcan et al, 2009;Sadaghiani, 2005;Shadmi, 1978;Singh, 2001;Singh et al, 2006;Strnad, 1981;Styer, 1996;Vandegrift, 2002;Wattanakasiwich, 2005).…”
Section: Pedagogical Research On Quantum Theorymentioning
confidence: 99%